Fast texture synthesis via patch-based circular linked lists - Xiong Changzhen; Guo Fenhong (2009 IEEE Pacific Rim Conference on Communications, Computers and Signal Processing, 2009)
A novel texture synthesis method is proposed to form large textures. The task of texture synthesis is divided into two phases: analysis, and synthesis. During the analysis phase, we generate patch-based circular linked lists (PCL) by recording the process of texture synthesis based on graph cuts. The main task of synthesis phase is to pick up patches and copy them to the output to synthesize textures using the PCL. The PCL algorithm synthesizes high-quality textures ranging from regular to stochastic. Compared with the jump map method, our approach is better capturing of texture characteristics and thus performs well when the jump map algorithm fails to produce good results.